EKSISTENSI UANG KETON SEBAGAI ALAT TUKAR BELANJA PADA PASAR WARISAN PULAU PENYENGAT - Rachmad Chartady; Muhammad Isa Alamsyahbana; Armansyah Armansyah; Eka Kurnia Saputra (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Tourism is a manifestation of the symptoms of human instincts long ago, namely the desire to travel. This is also the reason for Penyengat Island to continue to develop its tourist attraction because it is an amazing place and keeps a combination of tourism between history, spectacular nature and cultural arts that are so compelling. At present, Penyengat Island has a new tourist destination, the heritage market which is the second year this destination has been established. One of the uniqueness of the inheritance market is the existence of transactions using ketone money which was used as a medium of exchange for shopping during the Malay kingdom. Visitors can exchange rupiah for Ketone money to buy food, goods or souvenirs. The purpose of this research is to find out how ketone money can be used as a shopping transaction tool. With the service method in the form of approaches and outreach to the public and visitors to the island of Penyengat. Stinging Legacy Exploration Activities are carried out in a day with a total of 400 participants. The expected outcome of this activity is that the local community and visitors of the stinging island can understand how to shop or trade using ketone money